Regulation of Drugs in Kerala: A Overview - KEMPAIAH SURESH; BALAMURALIDHARA V (International Journal of Pharma and Bio Sciences, 2018)
Kerala has been one of the pioneer States in India with an exemplary track record in the field of pharmacy. The Central Drug Control Standard Organization (CDSCO)generally concerned with policy & making of laws and rules, licensing work such as approval of licence meant for manufacture of Large Volume Parenteral, Vaccine & Sera, Blood Bank and Blood Components, Medical devices and products manufactured by Recombinant technology, gives clearance to new drug clearance, clinical trials, import registration, import of drugs etc., and inspections. The State drugs control department deals with licensing of both manufacturing and sales establishments of Drugs & Cosmetics. Drugs Control Administration regulates the manufacture, sale and distribution of drugs to ensure their quality and efficacy. Drugs Regulation in India is governed by the Drugs and Cosmetics Act, 1940 and it has been the focus of several recent policy reforms efforts in India, starting with Mashelakar Committee Report in 2013 to most recent report of Ranjit Roy choudhary report in 2013. nevertheless the regulatory structure continues to be plagued with several structural challenges, including issues related to regulatory harmonisation between centre ant the states, transparency, which have been undermined the general effectiveness of the regulatory system. This study, evaluates the administrative structure and functions of drug regulatory authorities at state level.